Trends in the development of nuclear medicine in the Russian Federation for 2015–2020 - L. A. Chipiga; E. R. Ladanova; A. V. Vodovatov; I. A. Zvonova; A. A. Mosunov; L. T. Naurzbaeva; S. A. Ryzhov (Радиационная гигиена)
The federal forms of statistical reporting (3-DOZ form, form No. 30 of the Ministry of Health of the Russian Federation and radiation-hygienic passports of the subjects of the Russian Federation for 2015–2020) were analyzed in order to estimate the current status of nuclear medicine and assess the perspective and developing proposals for improving the national system of radiation protection in nuclear medicine. Over the past six years, the number of radionuclide examinations in the Russian Federation has been at the same level: on average 530 thousand per year. In 2020 the number of examinations decreased that was caused by the epidemic of coronavirus infection. The largest number of examinations in 2015-2020 were performed in Moscow (21%) and St. Petersburg (11%). Federal medical centers equipped with high-tech equipment are located in these cities, and patients from different regions are examined in these centers. The examination of bone is the most common examination in Russia: 40% from all of nuclear medicine examination; there is a moderate increase of that examinations. There is a high number of renal examinations (17%). The next most frequent are examinations of myocardium, thyroid, liver and lungs; the number of these examinations are decrease. Due to the development of modern diagnostic technologies, installation of new positron emission tomography departments and replacement of the old equipment with the new one (decrease in the number of renographs and increase the number of positron emission tomographs), the number of “other” examinations are increased with a factor of 3.7 since 2015 but the number of “functional” examinations is decreased. About two thousand studies per year were examined on a scanner (renograph, gamma camera, single-photon emission tomography), and about 0.6 thousand hybrid imaging examinations per year were performed on a single-photon emission tomography combined with computed tomography. The annual collective dose of radionuclide diagnosis in the country has increased from 1.2 to 3.7 thousand man-Sv since 2015. The main contribution to the collective dose in Russia was associated with “other” examinations, which include hybrid imaging and whole body positron emission tomography: 55% (39% in St. Petersburg, 60% in Moscow). Due to the limitations and heterogeneous content of the federal forms of statistical reporting it is difficult to assess the current state of nuclear medicine in the Russian Federation. The authors of the study were updated of the data collection system in the radionuclide diagnosis in 3-DOZ forms; it is under approval. For detailed and reliable assessment of the nuclear medicine in the country, it is necessary to conduct a separate survey to determine the types of nuclear medicine examinations, the gender and age profile of patients and patient doses. That survey should be conducted in St. Petersburg or Moscow, as model subjects of the Russian Federation.